Research on sociocultural influences on motivation and learning. Volume 1 - Van Etten, Shawn (Research on sociocultural influences on motivation and learning, 2004)
The aim of this book series is to provide a much needed outlet for the wealth of cross-cultural research that has not impacted upon mainstream education. This particular volume is divided into four parts: the motivation context; the learning context; the family context; and the curriculum context.